Tips Menulis Artikel dan Memilih Jurnal yang Tepat bagi Mahasiswa Institut Bakti Nusantara - Eka Pariyanti; Rinnanik (PT. Berkah Digital Teknologi, 2024)
Scientific article writing is an essential skill for students to support academic and professional success. Despite its importance, many students face challenges in formulating ideas, writing coherently, and selecting appropriate journals. To address these needs, Institut Bakti Nusantara Lampung conducted a Community Service Program (PKM) titled